2022
DOI: 10.3390/diagnostics12051052
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Lower Extremity Length and Angle between Computed Radiography-Based Teleoroentgenogram and EOS® Imaging System

Abstract: Background and objectives: The differences between computed radiography-based teleoroentgenograms (CR-based teleoroentgenograms) and an EOS® imaging system were evaluated by measuring lower extremity lengths and alignments. Materials and methods: The leg length [L], femur length [F], tibia length [T], and hip–knee–ankle (HKA) angle were measured in 101 patients with lower extremity disease by a CR-based teleoroentgenogram with computed radiography and an EOS®. The additive length of the femoral and tibial segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The results showed that around 1/6 of patients exhibited a leg length discrepancy (LLD) exceeding 10 mm when measured from the lesser trochanter [ 25 ]. It was also shown that the average magnification for limb length measurement using Computed Radiography (CR) over EOS imaging was 6.8%[ 26 ]. In addition, it was found that conventional measurements of LLD on AP pelvic radiographs did not correlate well, while the full-length, functional imaging EOS method could provide a better evaluation of LLD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that around 1/6 of patients exhibited a leg length discrepancy (LLD) exceeding 10 mm when measured from the lesser trochanter [ 25 ]. It was also shown that the average magnification for limb length measurement using Computed Radiography (CR) over EOS imaging was 6.8%[ 26 ]. In addition, it was found that conventional measurements of LLD on AP pelvic radiographs did not correlate well, while the full-length, functional imaging EOS method could provide a better evaluation of LLD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiplanar deformities are common, but they may not be clinically significant. Statistical significance does not denote clinical significance [7]. Thus, the bulk of cases will seldom necessitate subsequent surgical correction.…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent the objective tools of scanogram imaging and computed tomography (CT) scans of both legs to assess longitudinal disturbances and multiplanar deformities; this is to ensure accurate assessment and appropriate alignment after surgery [7]. Several recent papers have used the supine CT scanogram to assess lower limb alignment, which has proved to have higher levels of accuracy compared to other methods.…”
Section: Methodsmentioning
confidence: 99%
“…Micro-dose digital radiography is computerized imaging that substantially reduces patients' radiation exposure compared to conventional radiographic techniques. In this method, a relatively old micro-dose digital technique [ 41 ], with a more recent development termed EOS (EOS imaging, Paris, France) [ 42 , 43 ], is used to measure limbs. Using a vertical gantry, the patient stands in front of the X-ray unit and remains still during the 20-second scanning process.…”
Section: Reviewmentioning
confidence: 99%
“…The source assembly and detector move together in a row-by-row motion so that the beam remains horizontal to the patient. Because the detector is efficient at finding and processing the point source of X-ray photons, the patient exposure, during the scan, was six to nine times lower than that of conventional radiographs and four to 23 times lower than that of CT [ 43 ].…”
Section: Reviewmentioning
confidence: 99%